Gravedad y condición epidemiológica de personas con dengue en hospitales de II y III nivel del MINSA Iquitos 2020 al 2022 - Moncada Rios, Lizeth Magaly (2025)
The objective was to determine the relationship between the severity and the epidemiological condition of patients with dengue treated in level II and III hospitals of the MINSA in Iquitos, during the period 2020-2022. A quantitative approach was applied with a non-experimental, descriptive and correlational, cross-sectional and retrospective design. The population was made up of 652 dengue patients treated in these hospitals, while the sample, determined using the formula for finite populations, included 242 people. Stratified probabilistic sampling with proportional allocation was used. The technique used was documentary review, and the instruments included a record sheet for the epidemiological condition of dengue and another sheet to identify the level of severity in the patients treated. SPSS statistical software version 24.0 was used for data processing, and the analysis was performed using the inferential Chi square test (X2). The results showed that 32.6% (79) of the patients were between 0 and 11 years old, 55% (133) were men, and 46.3% (112) had primary education. Additionally, 66.5% (161) were unemployed, 71.5% (173) were single, and 91.7% (222) reported no family history of dengue. Likewise, 93.0% (225) had no comorbidities, 95.9% (232) did not require oxygen, and 81.0% (196) were hospitalized for less than 7 days. Regarding origin, 49.6% (120) came from Punchana, 71.1% (172) received care in level III hospitals, 63.6% (154) were under emergency observation and 86.0% (208) presented dengue with warning signs. In conclusion, a significant statistical relationship was identified with age (p=0.003), the presence of comorbidities (p=0.009), the need for oxygen (p=0.000), the length of hospitalization (p=0.009), the type of health facility (p=0.012) and the hospital service (p=0.008).